Establishment of the 1st Chinese national standard for CA6 neutralizing antibody - Yiping Wang; Fan Gao; Zhenglun Liang; Huimin Sun; Junzhi Wang; Qunying Mao (Taylor & Francis Group, 2023)
Coxsackievirus A6 (CA6) is one of the major causative agents of herpangina and hand-foot-mouth disease (HFMD). Since 2008, CA6 has circulated widely around the world. Especially in Asia-Pacific region CA6 had even replaced enterovirus A71 (EV71) and coxsackievirus A16 (CA16) as the main prevalent strain of HFMD. In the recent 10 years, monovalent and multivalent vaccines against CA6 have been researched and developed by manufacturers from China, Korea, and the USA. The neutralizing antibody titer is a key indicator for accurately evaluating immunogenicity of vaccine. However, so far, the World Health Organization international standard for CA6 neutralizing antibody has not been available. In order to meet the needs of evaluating the immunogenicity of vaccines against CA6, the first Chinese national standard for CA6 neutralizing antibody was established, which was conducted to ensure that methods used to measure the neutralizing antibody titers against CA6 are accurate, reliable, and comparable. Three lyophilized candidate standards (29#, 39# and 44#) were produced with 0.40 ml/vial from plasma samples donated by healthy individuals. The collaborative study showed that the 29# candidate standard could effectively minimize the variability in neutralization titers between labs and across challenging viruses of different genotypes (A, D1, and D3). Therefore, the 29# candidate sample was established as the first Chinese national standard for CA6 neutralizing antibody test. This standard has good long-term stability and was assigned a potency of 150 units per milliliter (U/ml) of CA6 neutralizing antibody. It will contribute to ensure uniformity of potency or activity of vaccines and potentially therapeutic antibody preparations.